Influence of Hydrothermal Treatment on Physicochemical Properties and Drug Release of Anti-Inflammatory Drugs of Intercalated Layered Double Hydroxide Nanoparticles - Zi Gu; Aihua Wu; Li Li; Zhi Ping Xu (MDPI AG, 2014)
The synthesis method of layered double hydroxides (LDHs) determines nanoparticles' performance in biomedical applications. In this study, hydrothermal treatment as an important synthesis technique has been examined for its influence on the physicochemical properties and the drug release rate from drug-containing LDHs. We synthesised MgAl-LDHs intercalated with non-steroidal anti-inflammatory drugs (i.e., naproxen, diclofenac and ibuprofen) using a co-precipitation method with or without hydrothermal treatment (150 °C, 4 h). After being hydrothermally treated, LDH-drug crystallites increased in particle size and crystallinity, but did not change in the interlayer anion orientation, gallery height and chemical composition. The drug release patterns of all studied LDH-drug hybrids were biphasic and sustained. LDHs loaded with diclofenac had a quicker drug release rate compared with those with naproxen and ibuprofen, and the drug release from the hydrothermally-treated LDH-drug was slower than the freshly precipitated LDH-drug. These results suggest that the drug release of LDH-drugs is influenced by the crystallite size of LDHs, which can be controlled by hydrothermal treatment, as well as by the drug molecular physicochemical properties.